Dialogue bridges in the city (Journal of Planner and Development, 2020)
Since its establishment, cities have been looking for a special urban architectural language that distinguishes them from other cities and expresses their distinctive identity through continuous products through time and controls the totality of temporal and spatial changes through a bridging dialogue that manages the language of the city correctly, Which gives the stability of that language and its ability to adapt to the total changes that occur in the city over time, and thus the possibility of producing ideas integrated series and ideas are renewed overlapping with the legacy and bear multiple layers of meaning and signals and symbols create a total of two meanings The problem of research (not comprehensive studies to create a contemporary urban architectural language is ongoing. The strategy of bridging the dialogue is looking for a rich variation through the buildings that span over time such as architectural bridges The objective of the research was to find a modern urban architectural language in the city looking for a rich variation in urban bridges over time through a bridging strategy. Bridging is one of the tools of dialogue that includes the characteristics of bridges, tools, tools and indicators. The research was based on the objective of addressing the research problem in a way that provides for the possibility of achieving contemporary urban architectural language that achieves the objectives of the bridging strategy based on the management of dialogue and its mechanisms in Dealing with buildings that span the city as bridges of dialogue). For the purpose of verifying the hypothesis, a theoretical framework for dialogue, bridging, bridging strategy, and building over time, such as urban architectural bridges, were developed to define the vocabulary of the rules and mechanisms of the language To identify the value indicators of urban architectural bridges and to know the extent of the transformation of these bridges from the heritage to the contemporary on the basis of (consensus, discontinuity, variation) and to know the extent of the city’s ability to preserve its inherited urban architectural language while at the same time continuing with the present, A part of Al Nahr Street (located between Al-Mamoun Street and Al-Samawal Street) has been studied. The area contains extensive buildings rich in elements that represent the privacy of the language that goes through time and its ability to create a continuous language for the present and future.